Use of Conditionally Essential Amino Acids and the Economic Burden of Postoperative Complications After Fracture Fixation: Results from a Cost Utility Analysis - Shafrin J; Than KS; Kanotra A; Kerr KW; Robinson KN; Willey MC (Dove Medical Press, 2023)
Jason Shafrin,1 Kyi-Sin Than,1 Anmol Kanotra,1 Kirk W Kerr,2 Katie N Robinson,2 Michael C Willey3 1FTI Consulting, Center for Healthcare Economics and Policy, Los Angeles, CA, USA; 2Abbott Laboratories, Columbus, OH, USA; 3Department of Orthopedics & Rehabilitation, University of Iowa, Iowa City, IA, USACorrespondence: Jason Shafrin, Center for Healthcare Economics and Policy, FTI Consulting, Los Angeles, CA, USA, Tel +1 213-452-6483, Email Jason.Shafrin@fticonsulting.comObjective: To measure the economic impact of conditionally essential amino acids (CEAA) among patients with operative treatment for fractures.Methods: A decision tree model was created to estimate changes in annual health care costs and quality of life impact due to complications after patients underwent operative treatment to address a traumatic fracture. The intervention of interest was the use of CEAA alongside standard of care as compared to standard of care alone. Patients were required to be aged ≥ 18 and receive the surgery in a US Level 1 trauma center. The primary outcomes were rates of post-surgical complications, changes in patient quality adjusted life years (QALYs), and changes in cost. Cost savings were modeled as the incremental costs (in 2022 USD) of treating complications due to changes in complication rates.Results: The per-patient cost of complications under CEAA use was $12,215 compared to $17,118 under standard of care without CEAA. The net incremental cost savings per patient with CEAA use was $4902, accounting for a two-week supply cost of CEAA. The differences in quality-adjusted life years (QALYs) under CEAA use and no CEAA use was 0.013 per person (0.739 vs 0.726). Modeled to the US population of patients requiring fracture fixations in trauma centers, the total value of CEAA use compared to no CEAA use was $316 million with an increase of 813 QALYs per year. With a gain of 0.013 QALYs per person, valued at $150,000, and the incremental cost savings of $4902 resulted in net monetary benefit of $6852 per patient. The incremental cost-effectiveness ratio showed that the use of CEAA dominated standard of care.Conclusion: CEAA use after fracture fixation surgery is cost saving. Level of Evidence: Level 1 Economic Study.Plain Language Summary: Postoperative complications after fracture fixation adversely impact clinical outcomes and impose substantial economic burden. Conditionally essential amino acids (CEAA) have been shown to reduce postoperative complication rates, but the economic impact is unclear.In this study, we quantify the impact of CEAA on health care costs and quality of life related to postoperative complications.The model demonstrates significant cost savings ($4902 per year per patient with operative treatment for fracture fixation) from the use of CEAA supplementation. Improving health outcomes and reducing health care costs for patients undergoing operative treatment for fracture fixation will be increasingly important for health systems as US payers increasingly shift provider reimbursement towards value-based care.Keywords: postoperative complications, orthopedic surgery, fracture fixation, oral nutritional supplement, economic impact postoperative complications